CLEAN AND HEALTHY LIFESTYLE BEHAVIORS (PHBS) IN PREVENTION OF COVID-19. (Case Study on Poor Farmers in Rambeanak Village, Mungkid, Magelang, Central Java) - Aprilia Ningsih; Argyo Demartoto (Journal of Development and Social Change, 2021)
ABSTRACTAprilia Ningsih. D0317007. 2021. CLEAN AND HEALTHY LIFESTYLE BEHAVIORS (PHBS) IN PREVENTION OF COVID-19. (Case Study on Poor Farmers in Rambeanak Village, Mungkid, Magelang, Central Java). Skripsi. Advisor: Dr. Argyo Demartoto, M.Si. Sociology Study Program. Faculty of Social and Political Sciences. Sebelas Maret University. Surakarta.In December 2019, a case of pneumonia first appeared in Wuhan, Hubei, China. This disease attacks the respiratory system and can spread rapidly. Until now, many countries have been affected by the virus which is currently known as Corona Virus Disease (COVID-19). The existence of Covid-19 has an impact on all circles of society. One of them is for poor farmers in Rambeanak Village, Mungkid, Magelang, Central Java. Because most of them are elderly people who are susceptible to disease and viruses and work in dirty places. Of course they must implement Covid-19 prevention efforts such as conducting PHBS and implementing health protocols. This research was studied with Max Weber's theory of social action and used qualitative methods. Sampling based on purposive sampling. Data collection techniques by interview, observation, and supporting documents. Meanwhile, the validity of the data used source triangulation.The results of this study are: (1) Clean and Healthy Behavior in the prevention of Covid-19 in poor farmers is done by always doing hygiene. This cleanliness is carried out both within the scope of oneself and the surrounding environment. (2) The driving factor for poor farmers to implement PHBS is obeying government recommendations and the desire to always be healthy. (3) The factors that inhibit poor farmers from doing PHBS are the discomfort of wearing masks, keeping your distance, and forgetting. (3) The impact felt after implementing PHBS in an effort to prevent Covid-19 on poor farmers made them feel always healthy.Keywords: Supporting factors, Inhibiting factors, Impact, PHBS, FarmersPoor